Anti-amyloidogenic properties of an ethyl acetate fraction from Actinidia arguta in Aβ1–42-induced ICR mice. Issue 6 (22nd May 2018) - Ha, Jeong Su; Kim, Jong Min; Park, Seon Kyeong; Kang, Jin Yong; Lee, Du Sang; Lee, Uk; Kim, Dae-Ok; Choi, Sung-Gil; Heo, Ho Jin
Abstract : The anti-amnesic effect of an ethyl acetate fraction from Actinidia arguta (EFAA) on amyloid beta induced cognitive dysfunction. Abstract : This study aimed to investigate the ameliorating effect of an ethyl acetate fraction from the fruit Actinidia arguta (EFAA) on amyloid beta (Aβ)-induced neurotoxicity and cognitive deficits in ICR mice. EFAA showed potent protective effects against Aβ-induced neurotoxicity through 2′, 7′-dichlorofluorescein diacetate (DCF-DA), 2′, 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) and lactate dehydrogenase (LDH) release into the assay medium. EFAA treatment reduced the intracellular ROS level and lactate dehydrogenase (LDH) release in the mitochondria, and increased cell viability in Aβ-induced neuroblastoma MC-IXC cells. The administration of EFAA significantly attenuated Aβ-induced learning and memory deficits, which were evaluated by Y-maze, passive avoidance, and Morris water maze tests. Furthermore, EFAA showed the ameliorating effect of cholinergic functions by increasing acetylcholine (ACh) levels and decreasing acetylcholinesterase (AChE) activity, and protected antioxidant systems by increasing superoxide dismutase (SOD) and decreasing the oxidized glutathione (GSH)/total GSH and malondialdehyde (MDA) in the brain. Finally, EFAA prevented mitochondrial dysfunction via regulating apoptotic signaling molecules including phosphorylated Akt (p-Akt), phosphorylated tau (p-tau), Bax, and cytochrome c in the brain tissues. Therefore, the present study suggests that EFAA might be a potential source of natural antioxidants with the ability to ameliorate Aβ-induced amnesia.